Teachers' acceptance of the environmental education (EE) kit for teaching environmental education component in the classrooms - Sulaiman, Siti Hajar; Tengku Ismail, Tengku Hanidza; Juahir, Hafizan; Harun, Rosta (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
The teachers’ acceptance of the Environmental Education (EE) Kit was measured using three criteria: perception, attitude, and receptiveness. In this study, 81 teachers teaching Science, Geography, English and Malay Language from four public schools in Peninsular Malaysia who received the EE Kit participated. This study aimed to describe and analyze the experience of using the EE Kit for teaching environmental education component in the classroom. This study found that, 75/81 (92.59%) knew about the EE Kit, 64/81 (79.01%) used the EE Kit and 11 (13.58%) who knew about the kit but did not use it. Overall, teachers are in favor of the use of the EE Kit in the classroom and recommend it to be used in all schools in Malaysia.